2002
DOI: 10.1017/s0967199402002034
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis mediated by Fas receptor and activation of caspase-3 in MRL-+/+ or MRL-lpr/lpr murine oocytes

Abstract: The molecular mechanisms leading to ovarian follicular atresia in the typical pathways of programmed cell death remain to be clarified. Here we have demonstrated that the apoptotic signalling pathway in MRL-+/+ (MRL/+) murine oocytes is through the Fas receptor followed by the activation of caspase-3. In contrast, we found that the aberrant expression and dysfunction of the mutant Fas receptor in MRL-lpr/lpr (MRL/lpr) murine oocytes caused by insertion of the early transposable element (ETn) into the Fas gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Further observations demonstrated that the apoptosis in wild-type mouse oocytes is achieved through the Fas receptor followed by the activation of caspase-3. In contrast, the aberrant expression and dysfunction of the mutant Fas receptor in lpr mouse oocytes were associated with an inability to activate caspase-3 and thus fail to induce nuclear DNA fragmentation 39 . However, effects of FasL (gld) mutations on oocytes have not been reported.…”
mentioning
confidence: 92%
“…Further observations demonstrated that the apoptosis in wild-type mouse oocytes is achieved through the Fas receptor followed by the activation of caspase-3. In contrast, the aberrant expression and dysfunction of the mutant Fas receptor in lpr mouse oocytes were associated with an inability to activate caspase-3 and thus fail to induce nuclear DNA fragmentation 39 . However, effects of FasL (gld) mutations on oocytes have not been reported.…”
mentioning
confidence: 92%
“…In the bovine ovary, the Fas/FasL system may be regulated by gonadotropin-dependent mechanisms and may play a role during attrition, follicular regression, and atresia, because Fas antigen has been detected in oocytes from fetal and adult ovaries and in granulosa cells during the luteal phase (Guo et al, 2002;Kelkar et al, 2003). Fas ligand also mediates apoptosis in human granulose luteal cell cultures when these cells are pretreated with the Th1 cytokine, interferongamma (IFN-g) (Dzialo-Hatton et al, 2001;Huber et al, 2002).…”
Section: Introductionmentioning
confidence: 99%